Humic acids alleviate dextran sulfate sodium-induced colitis by positively modulating gut microbiota - Huang, Jiazhang; Xu, Pengfei; Shao, Mingzhi; Wei, Bin; Zhang, Cong; Zhang, Jie (Frontiers in Microbiology, 2023)
Humic acids (HAs) are natural polymers with diverse functional groups that have been documented and utilized in traditional Chinese medicine. Dextran sulfate sodium (DSS)-induced colitis has been used as a model to study inflammatory bowel disease. In this research, we investigate the effect of HAs on ameliorating DSS-induced colitis in mice. Our aim here was to investigate if HAs could be a remedy against colitis and the mechanisms involved. The results show that HAs facilitated a regain of body weight and restoration of intestinal morphology after DSS-induced colitis. HAs treatment alters the community of gut microbiota with more Lactobacillus and Bifidobacterium. Changes in bacterial community result in lower amounts of lipopolysaccharides in mouse sera, as well as lower levels of inflammatory cytokines through the Toll-like receptor 4 (TLR4)-NF-κB pathway. HAs also promoted the expression of tight junction proteins, which protect the intestinal barrier from DSS damage. Cell experiments show that HAs display an inhibitory effect on DSS growth as well. These results suggest that HAs can alleviate colitis by regulating intestinal microbiota, reducing inflammation, maintaining mucosal barriers, and inhibiting pathogen growth. Thus, HAs offer great potential for the prevention and treatment of colitis.